PENGARUH RUMAH PINTAR OMPU ANGGIAT YAYASAN MUAL HAPISTARAN (RUMPIN) TERHADAP MINAT BACA ANAK-ANAK DI DESA RAHUTBOSI KECAMATAN PANGARIBUAN - Eiraen Jane Gultom; Silvia Mariah Handayani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study analyzes the effect of the Ompu Anggiat Smart House of the Mual Hapistaran Foundation (RUMPIN) on children’s reading interest in Rahutbosi Village, Pangaribuan District. A quantitative descriptive method was employed with a total sample of 30 children aged 7–12 years participating in RUMPIN activities. Data were collected using a Likert-scale questionnaire and analyzed through validity and reliability tests, Kolmogorov–Smirnov normality test, simple linear regression, t-test, and coefficient of determination using SPSS. The regression equation (\hat{Y}=6.754+0.899X) with a significance value of 0.000 (<0.05) indicates a positive and significant effect. The (R^2) value of 0.531 implies that RUMPIN accounts for 53.1% of the variance in children’s reading interest. The findings confirm that RUMPIN significantly enhances children’s reading interest.